Ideology and Dissent among Economists: The Joint Economic Forecast of German Economic Research Institutes - Ha Quyen Ngo; Niklas Potrafke; Marina Riem; Christoph Schinke (Center for Economic Studies and ifo Institute (CESifo), 2015)
Economists, and also economic research institutes, differ in their attitudes towards desirability of economic policies. The policy positions taken can often be determined by ideology. We examine economic policy positions by investigating minority votes in the Joint Economic Forecast of German economic research institutes. The dataset consists of voting behavior over the period 1950-2014. Our results show that the German Institute for Economic Research (DIW Berlin) submitted by far the most minority votes, consistent with the popular impression that the DIW exhibits a preference for demand-oriented economic policy and has differed from the other leading economic research institutes in this respect. For example, the rate of minority voting of the DIW corresponded to some 300% of the rate of minority voting of the RWI Essen. Minority votes display an economic research institute's identity. When institutes are known to be associated with specific economic-policy positions, politicians, clients, and voters well understand how to assess the bias in the policy advice that is given.
Keywords: D72; I23; 330; decision making in committees; minority voting; policy preferences; ideology; Joint Economic Forecast of German economic research institutes